Budget deficit, inflation and economic growth in Nigeria: an empirical analysis (2022)
The taxonomy established by Wagner and Keynes on the effect of government expenditure on economic growth has continued to generate a series of empirical studies but so far no consensus has been achieved on the exact nexus between deficit financing and economic growth and when interacting with inflation variable. The study contributed to this debate by using the disaggregated Vector Autoregression (VAR) approach to investigate the impact of deficit financing on economic growth with inflation as an interaction variable. The study found, amongst others, that overall deficit financing had a positive and significant impact on economic growth when financed through external sources but had a deleterious effect when financed through domestic sources. This could be attributed to the crowding-out effect of the private sector when deficit financing is funded through the domestic loan market. The study also found that overall deficit financing is inflationary which also resulted in to decrease in real interest rates.